The Knowledge, Attitude, and Practice for Managing Infectious Waste Management during COVID-19 Pandemic: A Survey in Thailand - Bunjongsiri, Kultida; Sangaroon, Pathanin; Prasertchai, Araya; Pradisthaprecha, Anunya; Nakpan, Worrawit; Jiratkulthana, Saruda; Laoraksawong, Pokkamol (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 2 (2023): April-June 2023, 2023)
The coronavirus (COVID-19) pandemic, which started in late 2019, has had a significant impact worldwide. During the pandemic a massive amount of infectious waste has been produced, making the planning and creation of new waste management systems imperative. The objective of our research was to assess the Knowledge of, Attitude towards, and Practices (KAP) of, infectious waste management and disposal, particularly COVID-19 waste, of Thai people. This cross-sectional study was conducted over 6 months from October 2020 to April 2021. A self-administrated questionnaire was returned by 281 respondents and the data derived from the questionnaire was analysed using descriptive statistics. The results showed that 76.16% of respondents showed a good level of knowledge, 81.49% exhibited positive attitudes towards proper infectious waste management, and 43.77% of respondents had moderate practice levels. Analysis of the responses suggested that the ideal course of action for infectious waste management is to include the informal sector in strategies for managing infectious waste, drawing on their practices and knowledge while aiming to improve production and the living and working conditions of those involved. To lessen the risk of environmental contamination and the possibility of infection or harm to the general population, local authorities should develop a well-planned collection and transfer mechanism for infectious waste. Keywords: knowledge, attitude, practice, infection, COVID-19